Configuração e mobilização familiar nas escolas estaduais de educação profissional: entre disposições, escolhas e motivações. - Santos, Harlon Romariz Rabelo (2017)
This argumentative text aimed to investigate the configuration and family mobilization of the State Schools of Vocational Education (EEEPs) in Ceara, Brazil. These schools emerged starting in 2008 within an educational policy of promotion of high school integrated to vocational education. These schools appear singularly among the existing state public schools because they have a: selection of students and teachers; particular curriculum, physical structure and budget; full-time shift; dual certification (regular and technical courses); they offer paid internship. Besides present a profile of pupil with better socioeconomic conditions than the average of the students of the state public network. EEEPs also present better results in external evaluations and are positive in the imaginary of many students and families from Ceará who demand for schools that increase their competitive odds, both in relation to professional life and the access to higher education. Because of the family factors impact in the dynamics and school performance, it was decided to analyze the sociological profile of the families of these schools, as well as the parental mobilizations. The research took place between 2015 and 2016 and started with a historical, legal and contextual analysis on the model of these schools; followed by a descriptive analysis of general educational data of the public schools of Ceara, through the microdata of the Socioeconomic Questionnaire of the ENEM; and with exploratory interviews with staff schools and family members of three of these schools. Next, a field research was performed on two EEEPs located in Fortaleza. This research was done through direct observations, with a survey to the students and with semi-structured interviews with a group of parents. The discussion is situated theoretically between dispositional perspectives and rational actor theory, seeking integration of analysis. The data and the theoretical perspective adopted allow us to conclude that EEEPs families have a sociological profile different from the other families of regular public schools; That the choices, motivations, expectations and strategies of the students and their families form an impact factor on the school dynamics and performance of EEEPs; and that the entry and stay in these schools are marked by a specific way of how parents and students consider the EEEP model in the face of the general framework of school supply, where values and motivations are descriptors of the schooling strategies adopted and the family mobilization that aim a better educational and socio-professional insertion for you children in the short and long term, indicating that there is a complex school hierarchy even within the same educational network.